LEVELS OF AS, CD, CU, MN, SE AND ZN IN MUSCLE AND LIVER TISSUE OF CHEILODACTYLUS VARIEGATUS VALENCIENNES, 1833 “PINTADILLA” IN THE COASTAL AREA OF LIMA, PERU - Quintana Paetán, Sigfredo Alexander (2021)
The "pintadilla" (Cheilodactylus variegatus Valenciennes, 1833) is a marine species that grows near the coast and is caught by artisanal fishing for human consumption. The objective of this study was to determine the concentration of the elements As, Cd, Cu, Mn, Se and Zn in this species (muscle tissue and liver tissue) in the coastal zone of Lima. A total of 32 samples were collected, during 8 months (period from september 2018 to march 2019), in the Artisanal Fisheries Markets of Chorrillos and Ancon, determining the concentration ofthe mentioned elements by means of optical emission spectrophotometry with inductively coupled plasma (ICP-OES). In general, the highest average concentrations of elements were found in liver tissue compared to muscle tissue for both areas (cadmium and manganese were not detected in muscle tissue). It was evidenced that there is no significant difference between the means of the concentrations for the two sampling areas (with the exception of copper). Positive correlation was evidenced only in some of the elements under study.